2007
DOI: 10.1176/ajp.2007.164.2.265
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Controlled Clinical Trial of Psychoanalytic Psychotherapy for Panic Disorder

Abstract: Despite the small cohort size of this trial, it has demonstrated preliminary efficacy of panic-focused psychodynamic psychotherapy for panic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(78 citation statements)
references
References 23 publications
0
77
0
1
Order By: Relevance
“…It is of note that Berk and Parker [120] only referred to high-frequency long-term psychoanalytic therapy but did not include a discussion of manual-guided PDT. Several RCTs that fulfilled the criteria of Chambless and Hollon [8 ](table 1) included data on adverse events or side effects [40,43,47,49,50,52,55,64,74,77,95,122]. In these studies, adverse events or side effects were not more frequent in PDT than in the comparison treatments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is of note that Berk and Parker [120] only referred to high-frequency long-term psychoanalytic therapy but did not include a discussion of manual-guided PDT. Several RCTs that fulfilled the criteria of Chambless and Hollon [8 ](table 1) included data on adverse events or side effects [40,43,47,49,50,52,55,64,74,77,95,122]. In these studies, adverse events or side effects were not more frequent in PDT than in the comparison treatments.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the treatment of depression, Thase [[65], p. 954] concluded from the RCT by Driessen et al [50] that there is no evidence that PDT is a less effective treatment of MDD than CBT [95]. On the other hand, Milrod et al [43] found PDT to be superior to applied relaxation in panic disorder. Clarkin et al [44] reported PDT and dialectical behavior therapy to be equally effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of new treatments for panic attacks has been negligible in recent years (Stirman, Toder, & Crits-Cristoph, 2010). As studies of multiple methods of the treatment of panic attacks all report a significant number of subjects, 29% -48%, who do not experience a lessening of symptoms, the need for an approach such as the one described in this article is clear (Milrod et al, 2007).…”
Section: Introductionmentioning
confidence: 93%